2019
DOI: 10.1038/s41380-019-0449-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide methylation in alcohol use disorder subjects: implications for an epigenetic regulation of the cortico-limbic glucocorticoid receptors (NR3C1)

Abstract: Environmental factors, including substance abuse and stress, cause long-lasting changes in the regulation of gene expression in the brain via epigenetic mechanisms, such as DNA methylation. We examined genome-wide DNA methylation patterns in the prefrontal cortex (PFC, BA10) of 25 pairs of control and individuals with alcohol use disorder (AUD), using the Infinium® MethylationEPICBeadChip. We identified 5,254 differentially methylated CpGs (pnominal<0.005). Bioinformatic analyses highlighted biological process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 60 publications
(72 reference statements)
5
42
1
Order By: Relevance
“…For example, cg18362496 in H19 that was previously reported hypermethylation in AUD brain samples [61] showed a positive association with PEth in our blood sample (p = 0.03). A stress-related gene, KCNK6, that was previously associated with AUD in brain [31] was nominal significant in the same direction in our study (p = 0.04). However, the majority of significant CpGs for alcohol consumption differs between brain and blood samples.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…For example, cg18362496 in H19 that was previously reported hypermethylation in AUD brain samples [61] showed a positive association with PEth in our blood sample (p = 0.03). A stress-related gene, KCNK6, that was previously associated with AUD in brain [31] was nominal significant in the same direction in our study (p = 0.04). However, the majority of significant CpGs for alcohol consumption differs between brain and blood samples.…”
Section: Discussionsupporting
confidence: 86%
“…Epigenome-wide association studies (EWAS) have identified hundreds of DNAm CpGs in blood for alcohol consumption [25][26][27][28], alcohol use disorder (AUD) [29,30], stress-related alcohol consumption [31], and fetal alcohol syndrome [32][33][34][35]. A large number of CpGs in the blood have recently been reported to have associations with dietary folate and alcohol intake [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting studies have shown evidence for a role for epigenetic mechanisms (e.g., DNA hypermethylation) in the pathophysiology of AUD and associated maladaptive behaviors ( Warnault et al, 2013 ; Berkel and Pandey, 2017 ; Gatta et al, 2017 , 2019 ). In a previous study in the cerebellum of AUD patients, we reported a marked decrease in the amounts of the GABA A R δ subunit, which was associated with increased DNA methylation of the corresponding gene promoter ( Gatta et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, similar processes are thought to take place in BA, which is essentially initiated by environmental stimuli in adulthood or during development. Recent studies with genome-wide DNA methylation assays have unveiled alterations in methylation patterns in drug addiction patients compared with healthy subjects 28 , 29 . DNA methylation is an epigenetic process that regulates gene expression, and as such, it was thought that CpG sites on promoter regions play crucial roles in inhibiting gene expression 30 .…”
Section: Introductionmentioning
confidence: 99%